A combination of clinical and microbiological management of generalized aggressive periodontitis in primary teeth. A case report - Cunha, Robson Frederico [UNESP]; Machado, Alessandra C. [UNESP]; Watanabe, Simone [UNESP]; Freire, Isabelle R. [UNESP]; Goiato, Marcelo Coelho [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (Wiley-Blackwell, 2012)
International Journal of Paediatric Dentistry 2012; 22: 310316 Background. Generalized aggressive periodontitis (GAP) in primary teeth is a rare periodontal disease that occurs during or soon after eruption of the primary teeth. An association with systemic diseases is a possibility. Case Report. A 4-year-old Brazilian girl presented with GAP involving the entire primary dentition. The patient and her parents and sister were subjected to microbiological testing to identify the microorganisms involved in the disease. The patient underwent tooth extraction to eradicate the disease and received a prosthesis for the restoration of masticatory function. After the permanent teeth erupted, fixed orthodontic appliances were place to restore dental arch form and occlusion. Conclusions. The results show the importance of an early diagnosis of GAP and of a multidisciplinary approach involving laboratory and clinical management to treat the disease and to restore masticatory function, providing a better quality of life for patients.